ANALISIS PERENCANAAN OBAT ANTIBIOTIK DENGAN METODE ABC-VEN DI INSTALASI FARMASI RAWAT JALAN RUMAH SAKIT X - Purwaningsih, Neneng Sri; Rizki Imansari, Aulia Nadya; Maharani, Naura Arzetti (STIKes Kharisma Persada, 2025)
ABSTRACT Background: Drug requirement planning is the process of determining the quantity and timing of procurement for Pharmaceutical Preparations, Medical Devices, and Medical Consumable Materials based on the results of prior selection activities, to ensure the fulfillment of the principles of the right type, right quantity, right timing, and efficiency. Objective: TThis study aims to evaluate the planning of antibiotic drug procurement using the ABC VEN analysis method in the outpatient pharmacy installation at Ilanur Mother and Child Hospital. Method: The method used is descriptive non-experimental with ABC VEN analysis. Results: The results of the study showed that from the ABC analysis, group A had a percentage of drug items of 10.25% (4 drug items) and a percentage of budget value of 69.63%. Group B had a percentage of drug items of 20.52% (8 drug items) and a percentage of budget value of 21.32%. And group C had a percentage of drug items of 69.23% (27 drug items) and a percentage of budget value of 9.02%. The results of the VEN analysis with group V had a percentage of drug items of 51.28% (20 drug items). Group E had a percentage of drug items of 41.03% (16 drug items). Group N has a percentage of drug items of 7.96% (3 drug items). Conclusion: In this study, category A drugs are drugs that have the largest budget and category V is important drugs that must not run out. ABSTRAK Latar belakang: Perencanaan kebutuhan obat merupakan proses untuk menentukan jumlah serta waktu pengadaan Sediaan Farmasi, Alat Kesehatan, dan Bahan Medis Habis Pakai berdasarkan hasil seleksi yang telah dilakukan, guna memastikan terpenuhinya prinsip tepat jenis, tepat jumlah, tepat waktu, serta efisien. Tujuan: Penelitian ini bertujuan untuk mengevaluasi perencanaan pengadaan obat antibiotik dengan menerapkan metode analisis ABC VEN pada instalasi farmasi rawat jalan di Rumah Sakit Ibu dan Anak Ilanur. Metode : deskriptif dengan pendekatan crossectional dengan pengambilan data secara retrospektif dan pengambilan sampel secara purposive. Hasil: Hasil penelitian menunjukan dari analisis ABC kelompok A memiliki persentase item obat 10,25% (4 item obat) serta persentase nilai anggaran 69,63%. Kelompok B memiliki persentase item obat 20,52% (8 item obat) serta persentase nilai anggaran 21,32%. Dan kelompok C memiliki persentase item obat 69,23% (27 item obat) serta persentase nilai anggaran 9,02%. Hasil analisis VEN dengan kelompok kelompok V memiliki persentase item obat 51,28% (20 item obat). Kelompok E memiliki persentase item obat 41,03% (16 item obat). Kelompok N memiliki persentase item obat 7,96% (3 item obat). Kesimpulan: Pada penelitian ini obat kategori A yaitu obat yang memiliki anggaran dana terbesar dan kategori V yaitu obat yang penting tidak boleh sampai habis.